A decision support system for sustainable and resilient water-energy-food management - Sikka, Alok; Sena, Dipaka Ranjan; Alam, Mohammad Faiz; Behera, Abhijit; Chaudhary, Shivam; Sharma, Ruchi; Chandu, Navya (2025)
The Water-Energy-Food (WEF) Nexus is increasingly recognized as a vital framework for addressing sustainability challenges, especially in regions facing growing pressure on natural resources and climate change. This paper introduces a Decision Support System (DSS) developed under the CGIAR Nexus Gains Initiative to support integrated WEF planning in India. The DSS integrates surface and groundwater models (SWAT+ and GWFLOW) with detailed land use and crop data to generate spatially explicit information on key hydrological and agricultural variables. The DSS includes a WEF Scenario Generator and a WEF Trade-off Index (WEFTI) calculator, which allow users to explore different interventions such as expanding irrigated area, crop diversification, and improvements in irrigation efficiency and other scenarios while evaluating their implications across water, energy, food, and ecosystem. The tool has been applied in the Ganges River Basin, India to demonstrate how such a framework can support local and regional decision-making, helping to prioritize interventions that contribute to nexus gains and sustainable development goals. The WEF-Nexus DSS is useful in making policy decisions for improving cross-sectoral planning and resource management in complex and resource constrained environments.